Does molecular analysis increase the efficacy of bronchoalveolar lavage in the diagnosis and management of respiratory infections in hemato-oncological patients?. (September 2016) - Oren, Ilana; Hardak, Emilia; Zuckerman, Tsila; Geffen, Yuval; Hoffman, Ron; Yigla, Mordechai; Avivi, Irit
Highlights: Fiberoptic bronchoscopy with bronchoalveolar lavage (FOB-BAL) provided a diagnosis in 51.5% of hematological malignancy patients with pulmonary infiltrates. The improved yield of FOB-BAL relates to the employment of molecular techniques. The most common infectious diagnosis was invasive aspergillosis. Summary: Objectives: The identification of the specific pathogen responsible for a respiratory infection in patients with hematological malignancies (HM) would ensure relevant treatment and prevent toxicity associated with anti-infective therapy. This large-scale study aimed to explore the clinical impact of fiberoptic bronchoscopy with bronchoalveolar lavage (FOB-BAL) in conjunction with molecular analysis on the diagnosis and management of respiratory infections in hemato-oncological patients. Methods: All consecutive patients with HM and pulmonary infiltrates, who underwent FOB-BAL between January 2008 and January 2013, were included in the analysis. Clinical characteristics, FOB-BAL results, and treatment adjustments were recorded, and factors predicting a positive BAL were assessed. Results: Four hundred and twenty-five FOB-BAL procedures were analyzed. BAL revealed a specific diagnosis in 219 (51.5%) patients, 208 of them with a pulmonary infection. Infectious etiological agents found were mainly Aspergillus spp ( n  = 142), bacterial species ( n  = 44), and Pneumocystis jirovecii ( n  = 34). Multivariate analysis showed that a lymphoproliferative disease, ≥2 symptoms (dyspnea/cough/hemoptysis/pleuritic pain), and less than 4 days between symptom appearance and FOB-BAL, predicted a positive FOB-BAL result. BAL results prompted a treatment modification in 48% of subjects. Conclusions: FOB-BAL in conjunction with molecular assays is efficient in the rapid detection of life-threatening infections, allowing for adjustment of anti-infective therapy, which may result in better outcomes and reduce treatment-related toxicity.